THE INFLUENCE OF PHYSICAL THERAPY ON INDICATORS OF LOCOMOTIVE SYNDROME IN ELDERLY PERSONS WITH OSTEOARTHRITIS OF THE KNEE AND OBESITY - Mariia H. Aravitska; Olesia V. Saienko (Клінічна та профілактична медицина, 2023)
Aim: to assess the effectiveness of the developed physical therapy program on locomotive syndrome parameters in elderly people with osteoarthritis of the knee and obesity.